2015
DOI: 10.1007/s11164-015-2177-0
|View full text |Cite
|
Sign up to set email alerts
|

UV excited green luminescence of SrAl2O4:Eu2+, Dy3+ nanophosphor

Abstract: Eu, Dy co-doped strontium aluminate nanophosphors were prepared by the combustion synthesis method. Their structure and morphology were investigated by X-ray diffraction (XRD), scanning electron microscopy, transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy. According to the XRD and the TEM analysis, the average crystallite size was found to be in the nanometer range. The phase structure of the prepared nanophosphor is consistent with a standard monoclinic phase with a space gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The latter band is shifted 10 nm upwards with respect to the blue site emission in dysprosium-free powder samples with the same concentration of europium (Figure S4b). , A red shift of the Eu blue site emission was already observed by Jia et al in single crystal fibers in the presence of dysprosium although no shift was observed in the presence of dysprosium in powder samples. , Other studies relate the blue shift to the particle size of the phosphor . Furthermore, the presence of trivalent ions within the crystal was studied by selective irradiation at 472 nm ( 6 H 15/2 – 6 H 7/2 transition of Dy 3+ ) and 522 nm ( 5 D 1 → 7 F 0 transition of Eu 3+ ), where no absorption from the Eu 2+ is expected.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The latter band is shifted 10 nm upwards with respect to the blue site emission in dysprosium-free powder samples with the same concentration of europium (Figure S4b). , A red shift of the Eu blue site emission was already observed by Jia et al in single crystal fibers in the presence of dysprosium although no shift was observed in the presence of dysprosium in powder samples. , Other studies relate the blue shift to the particle size of the phosphor . Furthermore, the presence of trivalent ions within the crystal was studied by selective irradiation at 472 nm ( 6 H 15/2 – 6 H 7/2 transition of Dy 3+ ) and 522 nm ( 5 D 1 → 7 F 0 transition of Eu 3+ ), where no absorption from the Eu 2+ is expected.…”
Section: Resultsmentioning
confidence: 90%
“…8,25 Other studies relate the blue shift to the particle size of the phosphor. 27 Furthermore, the presence of trivalent ions within the crystal was studied by selective irradiation at 472 nm ( 6 H15/2 -6 H7/2 transition of Dy 3+ ) 28 and 522 nm ( 5 D1→ 7 F0 transition of Eu 3+ ), 29 where no absorption from the Eu 2+ is expected. However, the strong emission due to the dipole allowed transitions from Eu 2+ masks the weaker f-f magnetic (and slightly electric) dipole allowed emission bands from Dy +3 and Eu 3+ ( Figures S3a and S3b).…”
Section: Resultsmentioning
confidence: 99%
“…This process will result in long afterglow. Therefore, more hole trap levels are created in SrAl 2 O 4 : Eu 2+ samples with higher Dy 3+ concentrations, leading to higher PL intensities [30]. Figure 5 displays the Commission International de L'Echairage (CIE) 1931 coordinates for Eu 2+ , Dy 3+ co-doped SrAl 2 O 4 excited at 337 nm.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Once the excitation light is removed, the light energy will gradually release out in the form of bright visible luminescence with green color, which is due to the characteristic 4f 6 5d 1 to 4f 7 transition of Eu 2+ ions that doped in the substrate of SAOED. 13 Besides, it is well known that fluorescence pigment (FP) can be excited by some certain lights with certain wavelength and then emit fluorescence with a certain color due to some special chemical groups in the molecular structure of the FP, such as the chromophore or auxochrome groups, carbonyl, azo z E-mail: ge_mingqiao@126.com and carbon-nitrogen bonds. 14 However, usually the lifetime of this fluorescence released by the FP is less than 0.5 μs, and after the light source is removed, the fluorescence will disappear immediately.…”
mentioning
confidence: 99%